PENGARUH RESIKO BISNIS DAN GROWTH OPPORTUNITY TERHADAP STRUKTUR MODAL PADA PERUSHAAN MANUFAKTUR SUB SEKTOR KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA PRIODE 2012-2017 - Deni Sunaryo (Jurnal Riset Akuntansi Terpadu, 2019)
Based on this aim is to determine the effect of business risk and growth opportunity on the capital structure of the cosmetics and goods manufacturing sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2012-2017. Based on the results of this study it can be concluded partially business risks have a significant effect on the capital structure of the cosmetics and household goods manufacturing sub-sector companies listed on the Indonesia Stock Exchange. This is evidenced by the results of the t test for business risk variables obtained t count 14.675 with the significance value of the study shows the number 0.000. The results of the study show that partially the growth opportunity does not have a significant effect on the capital structure of the cosmetics and household goods manufacturing sub-sector companies listed on the Indonesia Stock Exchange. This is evidenced by the results of the t test -0.985 with the significance value of the study showing the number 0.333. Business risk and growth opportunity significantly influence the capital structure of the cosmetics and household goods manufacturing sub-sector manufacturing companies listed on the Indonesia Stock Exchange with an F count of 113.531 with a significance value of 0.000. The value of the adjusted R Square number determination coefficient shows that business risk and growth opportunity on capital structure is 89.4% while the remaining 10.6% is explained by other factors outside the research model. Based on this aim is to determine the effect of business risk and growth opportunity on the capital structure of the cosmetics and goods manufacturing sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2012-2017. Based on the results of this study it can be concluded partially business risks have a significant effect on the capital structure of the cosmetics and household goods manufacturing sub-sector companies listed on the Indonesia Stock Exchange. This is evidenced by the results of the t test for business risk variables obtained t count 14.675 with the significance value of the study shows the number 0.000. The results of the study show that partially the growth opportunity does not have a significant effect on the capital structure of the cosmetics and household goods manufacturing sub-sector companies listed on the Indonesia Stock Exchange. This is evidenced by the results of the t test -0.985 with the significance value of the study showing the number 0.333. Business risk and growth opportunity significantly influence the capital structure of the cosmetics and household goods manufacturing sub-sector manufacturing companies listed on the Indonesia Stock Exchange with an F count of 113.531 with a significance value of 0.000. The value of the adjusted R Square number determination coefficient shows that business risk and growth opportunity on capital structure is 89.4% while the remaining 10.6% is explained by other factors outside the research model.